On-line monitoring of base metals solutions in flotation using diffuse reflectance spectrophotometry - Phiri, Mohau Justice (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2010.